Catalytic combustion of volatile organic compounds on pillared interlayered clay (PILC)-based catalysts. (June 2018) - Li, Jingrong; Hu, Maocong; Zuo, Shufeng; Wang, Xianqin
Graphical abstract: Highlights: Review the development of modified PILC from single-core to multi-core. Discuss the advantages/disadvantages of different synthesis method for PILC modification. Outlook on the industrial application of PILC-based catalysts on VOCs elimination. Abstract : Pillared interlayered clay (PILC) is one type of structure-controllable two-dimensional layered porous material with high specific surface area, large interlayer spacing and good heat-resistant stability. Due to these excellent structural characteristics, PILC has attracted intense interests and become an active research topic in recent years. Structure controllability and performance optimization are two major pending issues, while pore structure and heat-resistant stability are considered as the critical factors. The applications of PILC-based materials for catalytic combustion of VOCs is intensively studied in recent years. In this article, common synthetic approaches to prepare PILC are reviewed and the development from a single-core pillar to a multi-core pillar is summarized. Their applications in adsorption/desorption/catalytic combustion of volatile organic compounds (VOCs) are discussed. Finally, future application prospects of the PILC-based catalysts are covered. This review provides key information to our community to design and fabricate PILC-based catalysts with great performance.